Blade Runner: postmodern representations of the gaze and the approximations between the self and the Other in Cyberpunk - Wurmli, Robert Thomas Georg (2024)
The aim of this article is to evaluate how Cyberpunk conceives of postmodernity, especially through its most classic works To this end, the purpose of this article is to investigate the way in which the film Blade Runner promotes debates related to postmodernity, specifically with a view to analyzing the configurations of the characters and the process of rejecting the Other. We believe that, in post-modernity, the opportunity for alterity lies in the analysis and understanding of works from the cyberpunk universe, precisely because they deal with hybrid, peripheralized subjects who are commonly segregated in artistic representations to secondary roles. In this way, these works encapsulate many of the problems and forms of prejudice that are still perceived in post-modern societies. The aim here is to provide a basis for an interpretation of the film Blade Runner as an example of this classic format for the genre, based on a simple premise: how the gazes and designations of the characters absorb and sustain debates about our way of coexisting. The contributions of Dyens (2000), Flisfeder (2021), Jameson (1995) and Zizek (1993) will be used to further this inquiry.